Navigating resilience: Mental health self-care among middle-aged and older LGBTQ+ adults in Thailand - Nanchatsan Sakunpong; Ramida Mahantamak; Chawitra Tantimala; Kitsiri Chochiang; Sarah Abboud (PLoS ONE, 2026)
Introduction This study explores how middle-aged and older LGBTQ+ adults in Thailand engage in mental health self-care within complex social and cultural environments. While global research has largely reflected Western perspectives, little is known about how self-care is practiced in non-Western, Buddhist, and collectivist contexts. This study situates mental health self-care as both an individual and socially embedded process shaped by cultural beliefs, kinship norms, and structural inequalities. Methods A qualitative study was conducted with 30 LGBTQ+ participants aged 50–68 from Thailand, using thematic analysis. Semi-structured, in-depth interviews were carried out online and analyzed within a thematic framework to identify recurring patterns and culturally grounded meanings. Results Two overarching themes emerged: (1) Socio-cultural backgrounds shaping mental health self-care, which included Family and Childhood Memories, Community Environment, Cultural Beliefs and Mental Health, and Intimacy and Romantic Experience; and (2) Lived Experiences of Mental Health Self-Care, encompassing strategies for Coping with Stigma and Discrimination, Barriers to Mental Health Services, Cultivating Joy, Pride, and Self-Reliance, Community Contribution and Advocacy, Physical Health as Mental Anchor, and Self-Education on Mental Health. Self-care was intertwined with Buddhist ethics, caregiving norms, and digital peer support, reflecting both adaptation and quiet resistance within Thai society. Conclusion Mental health self-care among older LGBTQ+ Thais represents a culturally informed resilience that bridges individual agency and collective well-being. The findings highlight the importance of integrating social determinants of health and cultural context into inclusive mental health policies and community-based interventions for aging LGBTQ+ populations.